2018
DOI: 10.4236/ajps.2018.94064
|View full text |Cite
|
Sign up to set email alerts
|

Early Forage Biomass and Sward Structures of Native Warm-Season Grasses Established at Different Seedling Densities

Abstract: Effects of transplanted seedling density and species on sward structure of native warm-season grass (NWSG) stands were compared in a randomized complete block design. About 6-week-old NWSG (big bluestem (BB, Andropogon gerardii Vitman), eastern gamagrass (GG, Tripsacum dactyloides L.), indiangrass [IG, Sorghastrum nutans (L.) Nash] and switchgrass (SG, Panicum virgatum) seedlings were transplanted in 45-cm wide rows on clean-tilled seedbeds. Within-row spacing was 30, 25, or, 20 cm giving 10, 12, and 15 plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Our results of lower mean biomass yield of GG than SG were consistent with Backus et al (2017) who reported that SG produced ~7-8 Mg ha −1 while GG produced ~4-6 Mg ha −1 . Similarly, Temu et al (2018) reported SG biomass of 7.2 and 5.0 Mg ha −1 for GG. Switchgrass biomass can vary greatly in the literature, for example, ranging from as low as 1 Mg ha −1 to as high as 40 Mg ha −1 , because of differences in the varieties and ecotypes, agricultural practices, and harvesting stages used across different studies (Wullschleger et al, 2010).…”
Section: Grass Type Impact On Biomass Yield and Bioenergy Feedstock C...mentioning
confidence: 89%
“…Our results of lower mean biomass yield of GG than SG were consistent with Backus et al (2017) who reported that SG produced ~7-8 Mg ha −1 while GG produced ~4-6 Mg ha −1 . Similarly, Temu et al (2018) reported SG biomass of 7.2 and 5.0 Mg ha −1 for GG. Switchgrass biomass can vary greatly in the literature, for example, ranging from as low as 1 Mg ha −1 to as high as 40 Mg ha −1 , because of differences in the varieties and ecotypes, agricultural practices, and harvesting stages used across different studies (Wullschleger et al, 2010).…”
Section: Grass Type Impact On Biomass Yield and Bioenergy Feedstock C...mentioning
confidence: 89%